2014
DOI: 10.1039/c3em00728f
|View full text |Cite
|
Sign up to set email alerts
|

Application of diffusive gel-type probes for assessing redox zonation and mercury methylation in the Mekong Delta sediment

Abstract: The vertical profiles of PO4(3-), Mn, Fe, S(2-), Hg, and CH3Hg(+) in sediment pore water were investigated using DGT and DET probes in the Tien River, the northern branch of Vietnam's Mekong Delta. Although some of the DGT measurements could be lower than the actual pore water concentrations due to the depletion of the species, the measurements provided information for understanding redox zonation and Hg methylation. The gradual increases in the measured species concentrations with the sediment depth were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Rates of Hg uptake and accumulation onto the chelating resin are quantified and typically used to infer the “truly dissolved” concentration of Hg based on steady state diffusive uptake equations. 23 27 , 30 , 31 …”
Section: Introductionmentioning
confidence: 99%
“…Rates of Hg uptake and accumulation onto the chelating resin are quantified and typically used to infer the “truly dissolved” concentration of Hg based on steady state diffusive uptake equations. 23 27 , 30 , 31 …”
Section: Introductionmentioning
confidence: 99%
“…An arsenic/iron speciation and mobilization study using combined DGT (arsenic) and DET (iron) confirmed that arsenic mobilization was associated with the reductive dissolution of ferric (hydr)oxide in the sediment suboxic zone of 1 mm to 3 mm depth . The vertical profiles of Hg, MMHg, phosphate, sulfide, manganese, and iron were investigated using codeployment of DGT and DET probes in Mekong River sediments, and the maximum MMHg production was observed at a depth just above the maximum sulfide concentration . On the basis of the need for fine vertical resolution and high metal concentration to be collected, we conclude that DGT is one of the most reliable methods for measuring metal depth profiles in sediment porewater.…”
Section: Resultsmentioning
confidence: 96%
“…As with Hg, a flat probe was used to deploy the dissolved sulfide DGT in the sediment cores . The window on the probe provided a 1.8 × 24 cm 2 area for the diffusion of sulfide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, As speciation was investigated in anoxic sediment columns, using both DGT and DET (Diffusive Equilibrium in Thin films) (Bennett et al 2012). The DGT technique has not been applied yet to AD; nevertheless, it can be assumed that such applications would be similar to applications on anoxic sediments or soils (Hong et al 2014;Williams et al 2014).…”
Section: In Situ Methodological Applications For Free / Labile Metal mentioning
confidence: 99%